2015
DOI: 10.1111/tpj.13070
|View full text |Cite
|
Sign up to set email alerts
|

Development of two major resources for pea genomics: the GenoPea 13.2K SNP Array and a high‐density, high‐resolution consensus genetic map

Abstract: SUMMARYSingle nucleotide polymorphism (SNP) arrays represent important genotyping tools for innovative strategies in both basic research and applied breeding. Pea is an important food, feed and sustainable crop with a large (about 4.45 Gbp) but not yet available genome sequence. In the present study, 12 pea recombinant inbred line populations were genotyped using the newly developed GenoPea 13.2K SNP Array. Individual and consensus genetic maps were built providing insights into the structure and organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
225
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(231 citation statements)
references
References 76 publications
5
225
1
Order By: Relevance
“…1D). M. truncatula is a sequenced legume closely related to pea, and their genomes are collinear in this region (Tayeh et al, 2015). Reciprocal BLASTn searches of the M. truncatula genome (v4) and pea transcriptome databases showed that Crd is most similar to Med1g011630; they likely represent an orthologous pair.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1D). M. truncatula is a sequenced legume closely related to pea, and their genomes are collinear in this region (Tayeh et al, 2015). Reciprocal BLASTn searches of the M. truncatula genome (v4) and pea transcriptome databases showed that Crd is most similar to Med1g011630; they likely represent an orthologous pair.…”
Section: Resultsmentioning
confidence: 99%
“…Nat Protoc 1: 2320-2325 Alves-Carvalho S, Aubert G, Carrère S, Cruaud C, Brochot A-L, Jacquin F, Klein A, Martin C, Boucherot K, Kreplak J, et al (2015) Full-length de…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The advent of high-throughput next-generation sequencing (NGS) technologies with the possibility to sequence entire genomes more efficiently allowed to obtain large-scale SNP identification for crops and the onset of efficiency SNP genotyping platform (Schmid et al 2003;Dereeper et al 2011;Chagné et al 2012;Ganal et al 2012;Peace et al 2012;Verde et al 2012;Gardner et al 2014;Yu et al 2014;Tayeh et al 2015;Jiang et al 2016;Melo et al 2016). The abundance in the genome and the ability to identify polymorphism due to variation at single base level based on bi-allelic nature are the main advantages of SNP markers.…”
Section: Introductionmentioning
confidence: 99%
“…Our knowledge of plant transformation, plant genome evolution and breeding has increased dramatically in the past decades. We now know that breeding and mutagenesis are more unpredictable and cause more genome disruption than genetic engineering [10][11][12][13]. For instance, the comparison of genomic variation in transgenic plants to the genomic variation observed in cultivars and mutagenized lines revealed that, on average, the number of genes affected by structural variations in transgenics was one order of magnitude lower than that of fast neutron mutants and two orders of magnitude lower than between cultivars [10].…”
Section: The Compatibility Of Innovative Breeding Technologies With Omentioning
confidence: 99%
“…We believe it is time to reconsider this issue in the light of new insights on genomic dynamics during breeding and evolution obtained from the many genome sequencing data from the past decade [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%